Pricing behaviour of new listings on Bursa Malaysia during 1991-2000 / Chong Fen Nee... [et al.] - Nee, Chong Fen; Hok, Chong Vui; Duncan, William (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2005)
The equity market is an integral part of the capital market, enabling companies to raise capital through the issuance and sale of shares and other financial derivatives. It also enhances the marketability and liquidity of these financial instruments by providing the market for their trading. The past thirty years have witnessed numerous companies worldwide raising capital from the equity market, mostly through initial public offerings.(IPOs) IPOs may be undertaken in the form of new issues (the issuance of new shares for sale), offers for sale (the sale of previously issued shares by the owners of private companies) or a combination of new issues and offers for sale. The rapid increase in the number of IPOs worldwide are attributed to a number of factors. These included the growing awareness among private companies of the benefits of going public, the desire for larger capital bases to capitalise on opportunities, the efforts by national governments either to establish a national capital market or to enhance the efficiency and liquidity of the existing markets to enhance economic growth, the acceleration of the process of privatisation of government entities and the transition from socialist to market-oriented economies in many countries. Specific reasons for IPOs include the desire of companies to reduce the cost of new funds and to reduce the level of leverage. For the original owners of private companies, the reasons for undertaking IPOs include the desire to enhance the liquidity of their investments, realize part of the value of their investments and reduce their exposure to risk through reduction of their equity stake. Research interest on IPOs was motivated by three commonly observed phenomena pertaining to the price performance of new listings, namely the initial or short-run under-pricing, the 'hot issue' market phenomenon and the long-run under performance. The initial under-pricing phenomenon referred to the positive difference between the price of new listings on the first trading day with the offer price. The 'hot issue' market phenomenon relate to the observed pattern of recurring cycles in which periods of high positive initial returns were associated with increasing numbers of IPOs while periods of low positive and negative initial returns were associated with reducing number of IPOs. With regard to the third phenomenon, although the evidence of long-run under-performance were inconclusive, the frequency of their occurrence have led to a number of theoretical explanations being propounded. These included Miller's 'Divergence of Opinion', Shiller's 'Impresario' and Schultz's'Windows of Opportunity' hypotheses. This study examines the short-run price performance of a sample of 250 new listings on the main and second board of Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchange) from 1991 to 2000. Among the findings is that the new listings registered an average initial raw return of 89.7% and an average market-adjusted return of 90.4%. This finding is in line with the widely reported initial under-pricing phenomenon of new issues in both developed and developing stock markets worldwide. The degree of under-pricing is also within the range of 57.4% to 135% as reported by various studies on new listings on Bursa Malaysia. The study further found that new listings on the second board, with an average initial market-adjusted return of 96.4%, out-performed the 80.1% recorded by new listings on the main board. The study also found that while the average initial market-adjusted return varied substantially across different sectors, the variation was statistically insignificant. Likewise, it was found that the difference in the average market-adjusted return across listing years, although considerable, was statistically insignificant. Finally, the study found the existence of positive relationships between the market-adjusted initial return with the over-subscription rate, the operating history, the market condition, the listing board, privatisation and the amount of proceeds raised. However, only the relationships between the initial return with the over-subscription rate and the market condition were significant. The implication of this is that it would not be possible for investors to accurately predict the initial price performance of Malaysian new listings through analysing the ex-ante uncertainty factors.